TINJAUAN HUKUM EKONOMI ISLAM TERHADAP SISTEM PENGUPAHAN : Studi Pada Home Industry Roti Alfan Alfin Putatlor Gondanglegi Malang - adib, roisul; Lailatul Mukarromah (LP3M IAI Al-Qolam, 2024)
In the wage process, the conditions for wages must be carefully considered and of course they must also be in accordance with conventional wage provisions and Islamic economic law. Based on this background, the researcher wants to know what kind of wage system is practiced by the Alfan Alfin Breadhome industry and what is the review of Islamic economic law on the wage system implemented there. This is a field research. The sources of data used are primary data obtained from interviews and observations, and secondary data which is obtained from books related to the theme studied. The results of the research above are that the first wage for the Alfan Alfin Bread home industry applies a wage system based on unity or results, that is, the amount of wage received by employees is in accordance with the amount of production or results that have been obtained or produced by each employee as agreed before work. Where the wages are given every month. Secondly, Islamic law's review of this kind of wage system is valid as well as in accordance with the provisions because it is based on the principle of justice. The employees and business owners are mutually willing and do not feel disadvantaged.